REFLEKSI ABDULLAH SAEED TENTANG PENDEKATAN KONTEKSTUAL TERHADAP AYAT-AYAT ETHICO-LEGAL DALAM ALQURAN - Lestari, Lenni (At-Tibyan: Jurnal Ilmu Alqur'an dan Tafsir, 2017)
Awareness of the relationship between text, context and interpreters always experiences dynamics from time to time. From the classical to contemporary times, every interpreter always tries to present the results of interpretations that give benefit to anyone. The same is true for contextual interpreters, such as Fazlur Rahman, Amina Wadud, Muhammad Syahrur, and Khaled Abou El Fadl who will be briefly reviewed in this article. This article is the result of Abdullah Saeed's reflection on four contemporary commentators in interpreting the verses of legal ethics. Abdullah Saeed is an Australian scientist from the Maldives. Abdullah Saeed is also present to give a new color in understanding the Qur'an by taking into account the context of the revelation and context when the Qur'an was interpreted. This article is adapted from Abdullah Saeed's article entitled "Some Reflections on the Contextualist Approach to Ethico-legal Texts of the Quran" which he published in the Bulletin of SOAS. Therefore, this article seeks to find the vertices of Abdullah Saeed's reflection on some contextualist thinking ideas.